The kinematic analysis of 500m sprint start in 2005 world short track speed skating championship - Lee, C.-H.; Back, J.-H.; Lee, K. K. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
A field study was performed attempting a kinematic estimation for six female foreign skaters, who participated in the 500m female final round competition. The three dimensional motion analysis with DLT method was executed using four video cameras for analyzing the actual competition situation. The following conclusions are drawn; the elapsed time by phase in start motion of the foreign skaters appeared shorter than those of Korean skaters, so the start training of Korean skaters should be strengthened. Also the displacement of COG in the foreign skaters appeared shorter than those of Korean skaters. The velocity of COG and maximum velocity of skate blade of foreign skaters are faster than those of Korean skaters. And the foreign skaters showed the superior early velocity change.